Epidemiological Analysis of Environmental and Behavioral Risk Factors for Typhoid Fever Occurrence: A Case-Control Study at RSU PKU Muhammadiyah Delanggu, Klaten - Galih Muchlis Hermawan; Vita Susianawati; Firman Adhitya (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
This study aimed to analyze risk factors associated with the occurrence of typhoid fever at RSU PKU Muhammadiyah Delanggu, Klaten. The study employed a quantitative design with a case-control approach, involving 48 respondents consisting of 24 typhoid fever cases and 24 non-typhoid fever controls with a 1:1 ratio. The research instrument was a questionnaire covering respondent characteristics, personal hygiene, eating habits outside the home, and level of knowledge. Data analysis was conducted using univariate and bivariate analyses with the Odds Ratio (OR) test and a 95% Confidence Interval (CI). The results showed that gender was not significantly associated with the occurrence of typhoid fever (OR = 1.18; 95% CI: 0.38-3.66). Poor personal hygiene (OR = 11.40; 95% CI: 2.96-43.80), frequent eating outside the home (OR = 15.00; 95% CI: 3.64-61.90), and low level of knowledge (OR = 7.29; 95% CI: 2.04-26.10) were proven to be significant risk factors for typhoid fever. Therefore, promotive and preventive interventions focusing on hygienic behavior, food safety, and improvement of public knowledge are necessary to reduce the incidence of typhoid fever.